Determining patterns in the formation of a polymer shell by powder paint on wood surface - Tsapko, Yuriy; Likhnyovskyi, Ruslan; Buiskykh, Nataliia; Horbachova, Oleksandra; Mazurchuk, Serhii; Lastivka, Oles; Tsapko, Аleksii; Sokolenko, Kostiantyn; Matviichuk, Andrii (Eastern-European Journal of Enterprise Technologies, 2023)
An issue related to using wood and wood products for building structures is to ensure their stability and durability during operation within wide limits. Therefore, the object of this study was a change in the properties of the polymer shell of powder paint on wood during thermal modification. It is proved that in the process of thermal modification of wood, its structure changes, and accordingly, during the polymerization of powder paint, degassing occurs, which affects the polymer shell. Namely, during the thermal polymerization of powder paint at a temperature of 180 °C for untreated wood, shallow bubbles and craters are characteristic of the formed polymer shell. Instead, a smooth surface is marked for a sample of thermally modified wood. Thermogravimetric analysis data show thermogravimetric curves characterized by the loss of mass of the sample of the original wood with increasing temperature due to the processes of dehydration, destruction of hemicellulose and lignin. This is dehydration, accompanied by the destruction of the pyranose cycle, and carbonization to form a carbon residue and a complex mixture of volatile products. Due to this, bubbles and craters are formed in the polymer shell of the coating. Based on the obtained results of adhesion of the polymer shell on wood, which is treated with a mixture of epoxy polyester system with functional additives and a polymerization temperature of 180 °C, the adhesion level is 2.1 MPa. Reducing the polymerization temperature of a mixture of the epoxy polyester system with functional additives to 130 °C increases adhesion by 1.75 times, and the nature of the destruction passes through the polymer shell. For thermally modified wood, the level of adhesion is within 2.1 MPa, and the destruction takes place through the wood. This is due to the increased fragility of the surface after thermal modification of wood